PHYTOCHEMICAL STUDY AND IN VITRO ANTIOXIDANT ACTIVITIES OF HAMMADA SCOPARIA EXTRACTS FROM SOUTHEASTERN ALGERIA - Salah, Benkherara; O, Bordjiba (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: This study was carried out to determine the phytochemical constituents and to evaluate the antioxidant potential of the aerial part extracts of Hammada scoparia (Pomel) Iljin to validate the medicinal potential of this Algerian plant species. Methods: Crude extracts were prepared by cold maceration with absolute methanol and distilled water. Preliminary phytochemical screening is carried out to detect the presence of the major secondary metabolites using qualitative characterization methods. Quantitative estimation of total phenols, total flavonoids, flavanols, flavonols, and condensed tannins contents is performed using gallic acid, rutin, catechin, and quercetin as standards. In vitro antioxidant activity was evaluated by the free radical scavenging activity by 2,2-diphenyl-1-picrylhydrazyl (DPPH), trolox equivalent antioxidant capacity by scavenging of 2,2′-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical cation assay, and the ferric reducing power assay (ferric reducing antioxidant power). Results: Phytochemical screening showed the presence of alkaloids, flavonoids, tannins, terpenes and sterols, saponins, and anthocyanins. Total phenols were present more in aqueous crude extract (ACE) with 336.756±0.855 mg gallic acid equivalent/g DM. Total flavonoids and flavonols were more abundant in methanolic crude extract (MCE) than ACE. However, condensed tannins and flavanols were present less in MCE with only 0.958±0.052 and 4.547±0.055 mg CE/g DM, respectively. The ACE of this plant species had greater antioxidant activity than the other extract by DPPH and ABTS assays (35.823±0.129 and 51.323±0.394 mg trolox equivalent/g DM). The better ferric reducing power (2060.535±2.566 mM Fe+2/g DM) was also recorded with the same extract. Conclusion: ACE of aerial part of H. scoparia (Pomel) Iljin showed a high amount of secondary metabolites. The obtained results confirmed that the extracting solvent influenced the antioxidant property estimations of this plant. Hence, the ACE can be further exploited further for in vitro and in vivo research work.